A SEMIOTIC ANALYSIS OF SHAKESPEARE’S “O MISTRESS MINE” USING RIFFATERRE’S SEMIOTIC THEORY - Amalia, Desthia (Universitas Gunadarma, 2020)
Analyzing literature works has been widely known as a complex spectrum because the words choice and construction in any literature works can be done in free way. However, literature is known as a free instrument for people to express their feeling. The research discussed about a song entitled